A representação social da relação fé e política na escola Pe. Humberto Plummen - Silva, Lúcia de Fátima Gomes da (2008)
Our aim with this research is analyzing the social representation of the relation of faith and politics among the Christian militants, focusing the analysis at Priest Humberto Plummen Faith and Politics school of Regional Northeast 2 (CNBB National Conference of Bishops of Brazil). We identify the fundamental elements, the representation forms, searching realize how these elements interfere in the militancy of the liberation of attendants and congregated. The perspective that shows this work is based on the theory of the Social Representation, which concepts of objectivity and anchorage are highlighted and in other elements of field of the Science of Religion and the Sociology of Religion. We believe that such perspective supports the analysis of the social imaginary about the relation faith and politics present in the referring school, what reveals in the interviews made with students and coordinators. Thus, it is possible to verify if the social representation of faith is a constitutive element of its politic actions, as also check if the social representation of politics is a constitutive element of its expression of faith. And still if this relation supports a trace of identity that composes the ethos presents in the referring institution